The acquisition of object relative clauses in Spanish - Torrens, Vicenç (Frontiers in Communication, 2024)
The aim of this paper is to compare children's performance in a declarative object and subject relative comprehension task. Relativized Minimality proposes that object relative clauses are more difficult to process than subject relative clauses because they feature the intervention of the subject between the head and its trace. A comprehension test to 80 Spanish monolingual children aged from 4;6 to 7;10 was applied. Sentences with subject/object relative clauses when NPs had the same or different morphosyntactic features were tested. A significant statistical difference was found for the performance between object relatives and subject relatives, since the number of correct answers is higher in subject relatives (P<0.001). In addition, a significant statistical difference was found in object relatives between clauses that had the same or different morphosyntactic features, since the former were more difficult to understand (P<0.001). The fact that Object Relatives differed in number morphology facilitated the interpretation of the sentence.